An active oblique‐contractional belt at the transition between the Southern Apennines and Calabrian Arc: The Amendolara Ridge, Ionian Sea, Italy. Issue 11 (12th November 2014) - Ferranti, Luigi; Burrato, Pierfrancesco; Pepe, Fabrizio; Santoro, Enrico; Mazzella, Maria Enrica; Morelli, Danilo; Passaro, Salvatore; Vannucci, Gianfranco
Abstract High‐resolution, single‐channel seismic and multibeam bathymetry data collected at the Amendolara Ridge, a key submarine area marking the junction between the Apennine collision belt and the Calabrian subduction forearc, reveal active deformation in a supposedly stable crustal sector. New data, integrated with existing multichannel seismic profiles calibrated with oil‐exploratory wells, show that middle to late Pleistocene sediments are deformed in growth folds above blind oblique‐reverse faults that bound a regional pop‐up. Data analysis indicates that 10 to 20 km long banks that top the 80 km long, NW‐SE trending ridge are structural culminations above en echelon fault segments. Numeric modeling of bathymetry and stratigraphic markers suggests that three 45° dipping upper crustal (2–10 km) fault segments underlie the ridge, with slip rates up to 0.5 mm/yr. Segments may be capable with M 6.1–6.3 earthquakes, although an unknown fraction of aseismic slip undoubtedly contributes to deformation. The fault array that bounds the southern flank of the ridge (Amendolara Fault System) parallels a belt of Mw < 4.7 strike‐slip and thrust earthquakes, which suggest current left‐oblique reverse motion on the array. The eastern segment of the array shows apparent morphologic evidence of deformation and might be responsible for Mw ≤ 5.2 historic events. Late Pliocene‐Quaternary growth of the oblique contractional belt is related to the combined effects of stalling of Adriatic slab retreat underneath the Apennines and subduction retreat of the Ionian slab underneath Calabria. Deformation localization was controlled by an inherited mechanical interface between the thick Apulian (Adriatic) platform crust and the attenuated Ionian Basin crust.